Development of puzzle game as media for learning and profession interest - Rianto, Rianto; Setiawan, Retno Agus (International Journal Artificial Intelligent and Informatics, 2018)
Multimedia is one of means or media, component in multimedia can be images, text, video or sound. Multimedia can be used as a communication tool or convey of information to others. In this puzzle game, multimedia is used as a learning media to introduce the profession and know the professional interest for users. In addition, in this game there are elements of education, counseling and information about the importance of education. In this game, more devoted to 9th grade junior high school students. The value contained in this puzzle game is trying to direct students to continue their education to the highest level by presenting materials that are expected to give students an idea of the world of education, job opportunities junior, senior high school and university graduates